HUBUNGAN ANTARA EFIKASI DIRI DAN PENGAMBILAN KEPUTUSAN DENGAN KINERJA - Eka Febriantin (Universitas Negeri Jakarta, 2011)
The research aims to know about: (1) the correlation of self-efficacy with job performance; (2) the correlation of decision making with job performance; (3) the correlation of both self-efficacy and decision making with job performance. The research was done in state elementary school in Kecamatan Duren Sawit, East Jakarta. The method of this research is quantitative description approach. The purpose of using this method was to analyze the correlation between two or more variable through hypotheses test and also to research social phenomena in real situation. The results of the research are answering the hypotheses: (1) There’s a positive correlation of self-efficacy with job performance; (2) There’s a positive correlation of decision making with job performanc; (3) There’s a significance correlation of both self-efficacy and decision making with job performance. From the research result, it can be concluded that if self-efficacy of State Elementary School’s Principal increases, job performance will also increase. The same thing also happens to decision making. Therefore, the Principals’ self-efficacy and decision making ought to be improved in order to attain higher job performance. Finally, self-efficacy and decision making can simultaneously improve job performance. If they are applied, the Principal can attain better job performance.